(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The rapid development of financial technologies (fintech) has revolutionized the global financial ecosystem by offering more efficient, inclusive, and user-centric services. However, this digital transformation also brings a set of complex risks, including cybersecurity threats, data privacy violations, regulatory arbitrage, and operational vulnerabilities. This paper examines the major risk categories associated with fintech innovations and explores the regulatory challenges that arise in different jurisdictions. Through the analysis of global regulatory responses and comparative case studies, the article highlights the need for adaptive, technology-neutral frameworks to ensure sustainable fintech growth. Furthermore, it presents policy recommendations aimed at enhancing international cooperation, strengthening supervisory capacity, and ensuring the ethical use of emerging financial technologies.